REGULATORY PERSPECTIVE FOR GENE THERAPY PRODUCTS IN THE USA, EU AND JAPAN AND FUTURE ASPECTS - P. K., BALASUBRAMANYA; MISHRA, SANGITA; VENKATESH, M. P. (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Gene Therapy Products (GTPs) hold immense promise in revolutionizing medical treatments by altering genetic expressions to address various diseases. This study gives a summary of gene therapy products and their prospective uses, their historical development and several treatment options, as an in-depth exploration of the regulatory considerations for GTPs in the United States of America (USA), European Union (EU), and Japan, along with insights into future aspects of this field. A comprehensive discussion follows detailing the regulatory landscape and approval pathways in the USA, EU, and Japan. Programs that are exclusive to each area, such as PRIME (Priority Medicines) in the EU, USA's RMAT (Regenerative Medicines Advanced Therapy) designation and the Sakigake system in Japan are examined. Milestone meetings, approval requirements, and specific regulatory guidelines for GTPs in each region are also thoroughly covered. A list of approved GTPs and a glimpse into the future of the field. Anticipated trends include increasing investments, challenges related to production costs, expansion of manufacturing capabilities, and regulatory updates. The various regulatory strategies in each area and their efforts to balance patient access and safety will have a big impact on GTPs marketed in the future. Japan is well-positioned to maintain it’s as a global leader in regenerative medicine and cell treatments because of its favourable regulatory environment and government backing.